The Conceptual Relation of Electronic Word-of-mouth, Commitment and Trust in Influencing Continuous Usage of Social Commerce - Atyaf Sami Noori; Kamarul Faizal Hashim; Shafiz Affendi Mohd Yusof (International Review of Management and Marketing, 2016)
The advancement of social media has attracted businesses and firms to adopt and create a new type of commerce known now as social commerce (s-commerce). Within s-commerce, consumer's loyalty and returning to use have reduced mainly because it is a highly competitive environment, which is simply presented by products that are proposed and announced rapidly to the market. Electronic Word-of-Mouth (E-WOM), in s-commerce, plays a magic power because it enables consumers to make a collaborative decision. At the same time, it allows businesses to reach up their consumers and their related network in almost no cost and short time. Little is known about the effect of E-WOM on consumers' continuous use behavior. Hence, it is worth to propose a conceptual model to explain the relationship between e-WOM and continuous use behavior. Furthermore, this study explains the mediating role of trust and commitment on the relationship between e-WOM and continuous use behavior by adopting Commitment-Trust Theory. Additionally, this study examines flow experience determinants as predictors for promoting E-WOM among s-commerce consumers.